ETHICAL DILEMMAS OF RENEWABLE ENERGY - Uler-Zefikj, Monika; Filkoski, Risto; SHesho, Igor; Dimitrovski, Dame; Manev, Nikola; Spirkovska, Vera (University Ss. Cyril and Methodius in Skopje, 2022)
The world economic growth leads to increased energy needs that have to be satisfied with higher electricity production from both conventional and renewable energy sources. Due to the reduced fossil fuel stocks as well as environmental pollution caused by conventional power plants priority is given to the expansion of renewable energy sources. Motivated by the need to study the competitiveness, eco-friendliness and reliability of renewable en-ergy, research was conducted on the effect different energy types have on the environment, population, and economy. The aim of this paper is to analyze the ethical dilemmas of renewable energy as constraints for increasing the renewable energy share in the electricity generation and replacement of fossil fuels, considering the production process intensive-ness, noble materials depletion, and climate change caused. The extensive analysis showed that although renewable energy is in principle clean and inexhaustible energy source, it can cause burdens on nature and society.
Keywords: renewable energy